Correlations between Leaf Nitrogen, Phosphorus and Potassium and Leaf Chlorophyll, Anthocyanins and Carotenoids Content at Vegetative and Generative Stage of Bitter Leaf (Vernonia amygealina Del.) - Betty Tjhia; Sandra Arifin Aziz; Ketty Suketi (Journal of Tropical Crop Science, 2018)
Vernonia amygdalina Del. (Asteraceae) is a nutritional and medicinal plant that is used widely throughout tropical Africa and other countries. The leaves are proved to have strong antioxidant property. The concentration of chlorophyll a, chlorophyll b, anthocyanins and carotenoids in five different leaf positions of vegetative and generative phases were studied. The aim of the study is to understand and to correlate the content of the three nutrients and the bioactive compounds along the five leaf positions at vegetative and generative stage of the crop growth. The study showed that the concentration of chlorophyll a and b was higher, and anthocyanin concentration was almost zero in the generative than in the vegetative stage. The leaf concentration of N, P, and K were higher in vegetative than in generative stage. At vegetative stage, N positively correlated with chlorophyll a at the 1st leaf; K had strong correlations with anthocyanins at the 2nd and 3rd leaf and with chlorophyll a at the 2nd and 5th, and with chlorophyll b and carotenoids at the 5th leaf. At the generative stage, P had a strong positive correlation with carotenoids at 4th and 5th leaves, and K positively correlated with chlorophyll a and b at 5th leaf. The findings suggest that bitter leaf is better to be harvested at vegetative stage, and that potassium level is important to increase anthocyanins and carotenoids content.